Analisis dan Validasi Obat Metformin Dalam Plasma Manusia Menggunakan Metode HPLC - Mulidini Mulidini; Asri Yuniar Dwi Nanda; Nissa Khalida Hanum; Lina Nurfadhila; Marsah Rahmawati Utami (Journal of Pharmaceutical and Sciences, 2023)
Analytical method validation is a process that ensures accurate, specific, reproducible and stable analysis of the analytical range appropriate to the intended use. Analytical method validation include all procedur for that demonstrate quantitative measure of analytes such as from plasma. Determination of the concentration of a drug in plasma is complex because plasma is a complex matrix. The drug identified was metformin. Metformin is a drug orally antihyperglycemic agent used in the management of type II diabetes mellitus. Methods for quantitation of metformin in human plasma or in pharmaceutical form, one of which uses High Performance Liquid Chromatography (HPLC). HPLC is a liquid chromatography technique used to process various mixture components. This article review aims to make it easier for readers and future researchers to determine the presence of metformin in human plasma by using the HPLC analysis method accurately. This research method uses the literature review method using national journals and international journals through the google scholar database. Methods by KCKT or HPLC that can be used to validate the determination of metformin levels in plasma include RP-HPLC, HPLC, HPLC-UV, and U-HPLC. The most commonly used method with the best validity, efficiency and time estimation is RP-HPLC..